2016
DOI: 10.1016/j.stem.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Interference Efficiently Induces Specific and Reversible Gene Silencing in Human iPSCs

Abstract: Developing technologies for efficient and scalable disruption of gene expression will provide powerful tools for studying gene function, developmental pathways, and disease mechanisms. Here we develop CRISPR interference (CRISPRi) to repress gene expression in human induced pluripotent stem cells (iPSCs). CRISPRi, in which a doxycycline-inducible deactivated Cas9 is fused to a KRAB repression domain, can specifically and reversibly inhibit gene expression in iPSCs and iPSC-derived cardiac progenitors, cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
429
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(439 citation statements)
references
References 49 publications
10
429
0
Order By: Relevance
“…Cas9-mediated, iPSC-derived knockout cell lines for a variety of different genes have been reported for use in loss-of-function studies González et al, 2014;Smith et al, 2015;Liao et al, 2015;Chen et al, 2015b;Liang et al, 2015;Wang et al, 2015b). This technique can also be combined with CRISPRi to specifically, rapidly, and reversibly down-regulate specific genes in iPSCs and iPSC-derived cell types (Mandegar et al, 2016). Similarly, specific mutations have been introduced into iPSCs and iPSC-derived cells using Cas9 and HDR-mediated genome editing for the study of genetic diseases Hou et al, 2013;Rong et al, 2014;Smith et al, 2015).…”
Section: Genome Editing In Human Primary Cellsmentioning
confidence: 99%
“…Cas9-mediated, iPSC-derived knockout cell lines for a variety of different genes have been reported for use in loss-of-function studies González et al, 2014;Smith et al, 2015;Liao et al, 2015;Chen et al, 2015b;Liang et al, 2015;Wang et al, 2015b). This technique can also be combined with CRISPRi to specifically, rapidly, and reversibly down-regulate specific genes in iPSCs and iPSC-derived cell types (Mandegar et al, 2016). Similarly, specific mutations have been introduced into iPSCs and iPSC-derived cells using Cas9 and HDR-mediated genome editing for the study of genetic diseases Hou et al, 2013;Rong et al, 2014;Smith et al, 2015).…”
Section: Genome Editing In Human Primary Cellsmentioning
confidence: 99%
“…Recent evidence has convincingly shown that CRISPRi using dCas9-KRAB works much better than knock-out in terminating the gene expression by avoiding incomplete loss-of-function of the target gene and the presence of hypomorphic alleles [43]. By choice, CRISPRi might be even better than using multiple sgRNA to create a huge deletion in order to delete gene loci, which might result in a rearrangement in the chromosomal loci and lead to chromosomal instability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By choice, CRISPRi might be even better than using multiple sgRNA to create a huge deletion in order to delete gene loci, which might result in a rearrangement in the chromosomal loci and lead to chromosomal instability. An inducible dCas9-KRAB system is also available that enables a tetracycline-based gene repression [43].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Numerous web-based sgRNA design algorithms have facilitated the wide adoption of this technology [19,20], and the synthetic biology community and beyond have witnessed an explosion of new applications based on CRISPR/Cas9 [15,16]. For example, a nuclease-null variant of Cas9 (dCas9) has been fused to activator and repressor domains to generate designer transcription factors that can mediate constitutive expression (CRISPRa) or silencing (CRISPRi) of individual endogenous genes in various human cell types (Figure 1A,B) [1416,2123•]. In addition, simultaneous co-expression of multiple sgRNAs can direct sustained activation of multiple target loci to trigger genetic scripts, such as the differentiation of induced pluripotent stem cells (iPSCs) or the conversion of fibroblasts into neuronal cells [16,21,22].…”
Section: Adapting Genome-editing Tools For Mammalian Synthetic Biologymentioning
confidence: 99%